CAN'T RAISE ONE EYE BROW: DOES IT RING ANY NORWEGIAN BELLS?. Issue 12 (15th November 2016) - Galtrey, Clare; Schon, Fred; Modarres, Hamid; Rossor, Alexander; Lockwood, Diana; Reilly, Mary; Manji, Hadi
Abstract : A 60 year old Nigerian man with diabetes who has lived in Europe for 30 years but regularly revisits Nigeria, presented with 6 months of numbness and weakness in all four limbs and recent right facial weakness. Examination revealed partial right facial and left ulnar nerve palsies with areflexia but no skin lesions. Neurophysiology showed multifocal mixed sensory-motor neuropathy with demyelinating features and prominent facial nerve involvement. He was found to be HIV positive. Subsequent examination revealed peripheral nerve thickening confirmed on limb MRI. Nerve biopsy showed chronic endoneuritis and perineuritis, but no organisms were seen or cultured. He was diagnosed with pure neural borderline tuberculoid leprosy and treated with WHO leprosy multidrug therapy and HAART. This case illustrates the complexities of HIV-leprosy coinfection. Perhaps surprisingly leprosy infection is only subtly affected by HIV coinfection. Both HIV and leprosy cause neuropathies but coinfection is fortunately rare particularly in the UK. Here clinically grossly thickened nerves and neuropathological inflammatory changes in a patient from prevalent area strongly favoured the diagnosis of leprosy. It is not clear why HIV has such differing interactions between M.leprae and M.tuberculosis. Leprosy remains a major treatable diagnosis we need to keep reminding ourselves about.